The importance of Anísio Teixeira to the National Education - Lopes, Cristine Norbim Barcellos; Andrade, João Carlos Rodrigues (Revista Hipótese, 2015)
Review of the book “NUNES, Clarice. Anísio Teixeira. Coleção Educadores. MEC, 2010”.